Investigation of the magnetocaloric effect and phase transition in a newly discovered perovskite oxide La0.7Ba0.25Nd0.05Mn1-xZnxO3 for x = 0.03 and 0.05 - Dey Biswajit; Basu Arnab; Pal Soumyadipta; Kumar Sanjay (EPJ Web of Conferences)
In this study, we examine the magnetocaloric behavior of the newly discovered perovskite oxide La0.7Ba0.25Nd0.05Mn1-xZnxO3 (x = 0.03 and 0.05). We focus on key magnetocaloric parameters, such as magnetic entropy change, heat capacity change, full-width at half-maximum (FWHM), and relative cooling power (RCP) by analysing the temperature-dependent magnetization using a phenomenological model. The impact of Zn doping on both the magnetic properties and the magnetocaloric effect (MCE) is also investigated. As Zn concentration increases, the ferromagnetic to paramagnetic (FM-PM) transition temperature (TC) decreases, indicating a suppression of the magnetic behaviour. Notable changes in entropy and specific heat are observed around TC. We predict the MCE parameters by calculating the temperature-dependent magnetization data with varying external magnetic fields (H) using the model. The RCP values are 338.80 J / kg for x = 0.03 and 335.44 J / kg for x = 0.05 at a magnetic field of 50 kOe. All the results suggest that the material holds significant potential for magnetic refrigeration (MR) applications over a broad temperature range near room temperature. The Arrott plots confirm the second-order phase transition (SOPT) between the ferromagnetic and paramagnetic phases. Furthermore, the accuracy of the results and the reliable predictions of the MCE parameters validate the effectiveness of the phenomenological model.